Hemangioma presenting as a painful neck mass: A case report - Ansari, Sajid; Dhungel, K; Ahmad, K; Gupta, MK; Rauniyar, RK; Amanullah, Md. F (Journal of College of Medical Sciences-Nepal, 2014)
Hemangiomas of muscles are rare congenital benign vascular tumors usually seen on the trunk and extremities, but can also appear on the head and neck regions. In a young adult with soft tissue attenuation mass in the skeletal muscle, hemangioma should be considered in the differential diagnosis. Ultrasound and computed tomography are the useful imaging modalities for the diagnosing of hemangioma and complete surgical excision is the treatment of choice. We report a case of 24 year old woman with an intramuscular hemangioma involving the posterior neck muscles who presented to our department with painful neck mass. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 56-59 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9674